Compact Bandwidth-Enhanced 180-Degree Phase Shifter Using Edge-Coupled Multi-Microstrip and Artificial Transmission Line - Ding He; Jingxin Fan; Zhiqiang Zhu; Yang Yuan; Zhongjun Yu (Micromachines, 2023)
Compactness has obtained sufficient importance in wideband phase shifter design considerations, as it is directly related to fabrication cost. In this paper, a novel structure was presented to create compact broadband 180-degree phase shifter, which has the advantages of enhanced bandwidth and significantly reduced chip area. The proposed configuration consists of edge-coupled multi-microstrip lines (ECMML) and an artificial transmission line (ATL) with dual-shorted inductors, both of which have the periodic shunt load of capacitors. The ECMML can provide a high coupling coefficient, leading to an increase in the bandwidth, while the introduced capacitors can greatly reduce the line length (35.8% of the conventional method). To verify the relevant mechanisms, a wideband switched network with compact dimensions of 0.67 × 0.46 mm2 was designed via 0.15-micrometer GaAs pHEMT technology. Combined with the measured switch transistor, it was shown that the proposed phase shifter exhibits an insertion loss of less than 2 dB, a return loss of greater than 12 dB, a maximum phase error of less than 0.6° and a channel amplitude difference of less than 0.1 dB in the range of 10 to 20 GHz.